What are the potential enablers and barriers to cultivating self-directed lifelong learning in the workplace in Sub-Saharan economies – a South African case study? - Bhengu, Thabile (Graduate School of Business (GSB), 2024)
This research aimed to explore the aspects that either enable or inhibit the cultivation of selfdirected lifelong learning among adults within a working environment – which according to Illeris' interpretation is, “learning in the workplace that takes place in the encounter between the learning environments of the workplace and the employees' learning processes” (Illeris, 2004, p. 431). While previous studies often embrace an underlying assumption that individuals possess a pre-existing disposition to engage as lifelong learners, this study explored the progression towards it. The underlying research question was therefore approached from two levels, the orientation regarding lifelong learning, and the developed strategies to engage as a lifelong learner (Fischer & Kommers, 1999; Kirby et al., 2010). An investigation of the orientation level was intended to interrogate the mindset (deep-seated beliefs, opinions and understanding) held by the participants about lifelong learning, while the strategies level revealed the pre-existing lifelong learning strategies. The progressive development of both as the individual interacted with their respective organisations was then noted. Taken together, the impact of these levels was observed in terms of the individual's developed ability to engage as a lifelong learner, within and beyond their work environment. The above-mentioned research inquiry was undertaken by primarily observing the interaction of the adult (the participant working within the organisational environment) with their respective environment. Qualitative data was collected through semi-structured interviews and from secondary sources. The study focused on five South African small and medium enterprises (SMEs). From the core themes, the enablers and inhibitors which existed within the organisational environments were thereafter identified. Some features of the organisational environment which acted as strong enablers include loosely defined roles, team learning and the cultivation of individual agency. The clash of values between the organisation and the individual was one of the predominant inhibitors. One significant implication of this research is the recognition that both levels – lifelong learning orientation and strategies – were mutually dependent if an adult is to eventually engage as a self-directed lifelong learner.